Bilayer tablet technology: An overview - Divya .A, K. Kavitha, M. Rupesh Kumar, Dakshayani S, Jagadeesh Singh SD (Journal of Applied Pharmaceutical Science)
Over the past 30 years as the expense and complications involved in marketing new drug entities have increased, with concomitant recognition of the therapeutic advantages of controlled drug delivery, greater attention has been focused on development of sustained or controlled release drug delivery systems. Bilayer tablet is new era for the successful development of controlled release formulation along with various features to provide a way of successful drug delivery system
Keywords: Bi-layer tablet, push pull technology, tablet press, moisture sorption capacity